The Case for Anthocyanin Consumption to Promote Human Health: A Review. Issue 5 (10th September 2013) - Pojer, Elisa; Mattivi, Fulvio; Johnson, Dan; Stockley, Creina S.
Abstract Anthocyanins belong to the flavonoid group of polyphenolic compounds, which are responsible for the red and blue colors of plant organs such as fruits, flowers, and leaves. Due to their frequent presence in plants, particularly berry fruits, vegetables, and grapes, they are key components of the human diet. Interest in anthocyanins has increased widely during the past decade. Numerous studies have suggested that anthocyanins have a wide range of health‐promoting properties. These compounds are therefore considered to be a functional food factor, which may have important implications in the prevention of chronic diseases. The aim of this body of work is to investigate and review the current literature on anthocyanins, and particularly their pharmacokinetics and any health‐promoting properties, in order to summarize existing knowledge and highlight any aspects that require further study and analysis.